Effect of 0.02% and 0.01% atropine on ocular biometrics: A two-year clinical trial - Wang, Ming; Cui, Can; Yu, Shi-Ao; Liang, Ling-ling; Ma, Jing-Xue; Fu, Ai-Cun (Frontiers in Pediatrics, 2023)
Background Several studies have shown that various concentrations of low-concentration atropine can reduce myopia progression and control axial elongation safely and efficiently in children. The aim of this study was to evaluate the effects of 0.02% and 0.01% atropine on ocular biometrics. Methods Cohort study. 138 and 142 children were randomized to use either 0.02% or 0.01% atropine eye drops, respectively. They wore single-vision (SV) spectacles, with one drop of atropine applied to both eyes nightly. Controls (N = 120) wore only SV spectacles. Ocular and corneal astigmatism were calculated using Thibos vector analysis and split into J0 and J45. Results The changes in cycloplegic spherical equivalent refraction (SER) and axial length (AL) were −0.81 ± 0.52D, −0.94 ± 0.59D, and −1.33 ± 0.72D; and 0.62 ± 0.29 mm, 0.72 ± 0.31 mm, and 0.89 ± 0.35 mm in the 0.02% and 0.01% atropine and control groups, respectively (all P < 0.05). Both anterior chamber depth (ACD) and ocular astigmatism (including J0) increased, and lens power decreased in the three groups (all P < 0.05). However, there were no differences in the changes in ACD, ocular astigmatism, and lens power among the three groups (all P > 0.05). Intraocular pressure (IOP), corneal curvature, ocular astigmatism J45, and corneal astigmatism (including J0 and J45) remained stable over time in the three groups (all P > 0.05). The contributions to SER progression from the changes in AL, lens and corneal power of the three groups were similar (P > 0.05). The contribution of AL change alone to the change in SER was 56.3%, 63.4% and 78.2% in the above corresponding three groups. Conclusions After 2 years, 0.02% and 0.01% atropine had no clinical effects on corneal and lens power, ocular and corneal astigmatism, ACD or IOP compared to the control group. 0.02% and 0.01% atropine helped to control myopia progression mainly by reducing AL elongation.